On the Use of Response Chunking as a Tool to Investigate Strategies - Blume, Christopher L.; Boone, Alexander P.; Cowan, Nelson (Frontiers in Psychology, 2016)
In this perspective we suggest that chunking can be used as an investigative tool to determine the characteristics of other cognitive phenomena. We present an example of the usefulness of chunking multiple responses to aid in understanding object switch costs. Switch costs refer to the shorter response times for manipulation of the same item on two trials in a row compared to a switch between items. It is presently unclear if this result is due to structural or strategic processes. We provide a short review of past literature on switch costs and a proof-of-concept example that chunking may shed new light on this topic. We examined this question with boxes filled with numbers to be arithmetically updated and memorized. A situation in which there were two response items to be manipulated per trial eliminated or reversed the switch cost effect. We suggest that participants use a strategy in which the two output responses were chunked together, making it unfeasible to prepare separately for a repetition of the most recent item as participants do in other circumstances. Our data suggest that even a well-studied phenomenon can benefit theoretically from the use of chunking as a research tool.